Respuesta :
Answer:
Hyperbola Foci: [tex]\displaystyle (\pm \frac{\sqrt{37}}{2}, 0)[/tex]
Hyperbola Vertices: [tex]\displaystyle (\pm \frac{1}{2}, 0)[/tex]
Hyperbola Asymptotes: [tex]\displaystyle y = \pm 6x[/tex]
General Formulas and Concepts:
Math
- Simplifying
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
Algebra I
- Coordinates (x, y)
Pre-Calculus
Hyperbola Standard Form: [tex]\displaystyle \frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1[/tex]
- Center (h, k)
- Hyperbola Vertices: (±a, 0)
- Hyperbola Foci: c² = a² + b²
Hyperbola Asymptotes: [tex]\displaystyle (y - k) = \pm \frac{b}{a}(x - h)[/tex]
Step-by-step explanation:
Step 1: Define
[tex]\displaystyle 576x^2 - 16y^2 = 144[/tex]
Step 2: Rewrite
Rewrite equation into hyperbola standard form
- [Hyperbola] [Division Property of Equality] Divide 144 on both sides: [tex]\displaystyle \frac{576x^2 - 16y^2}{144} = 1[/tex]
- [Hyperbola] Split fraction: [tex]\displaystyle \frac{576x^2}{144} - \frac{16y^2}{144} = 1[/tex]
- [Hyperbola] Simplify: [tex]\displaystyle 4x^2 - \frac{y^2}{9} = 1[/tex]
- [Hyperbola] Rewrite: [tex]\displaystyle \frac{x^2}{\frac{1}{4}} - \frac{y^2}{9} = 1[/tex]
- [Hyperbola] Rewrite a and b: [tex]\displaystyle \frac{x^2}{(\frac{1}{2})^2} - \frac{y^2}{3^2} = 1[/tex]
Step 3: Identify Parts
Compare the general standard form and our equation standard form to identify parts of the hyperbola.
[tex]\displaystyle \frac{x^2}{(\frac{1}{2})^2} - \frac{y^2}{3^2} = 1[/tex] ↔ [tex]\displaystyle \frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1[/tex]
Hyperbola Center: (0, 0)
Hyperbola Vertices: [tex]\displaystyle (\pm \frac{1}{2}, 0)[/tex]
Step 4: Identify Other Parts
We go slightly more complex in determining the asymptotes and foci of the hyperbola.
Foci
- Substitute in variables [Hyperbola Foci]: [tex]\displaystyle c^2 = (\frac{1}{2})^2 + 3^2[/tex]
- [Hyperbola Foci] Evaluate exponents: [tex]\displaystyle c^2 = \frac{1}{4} + 9[/tex]
- [Hyperbola Foci] Add: [tex]\displaystyle c^2 = \frac{37}{4}[/tex]
- [Hyperbola Foci] [Equality Property] Square root both sides: [tex]\displaystyle c = \pm \sqrt{\frac{37}{4}}[/tex]
- [Hyperbola Foci] Simplify: [tex]\displaystyle c = \pm \frac{\sqrt{37}}{2}[/tex]
Our hyperbola foci are [tex]\displaystyle (\frac{\sqrt{37}}{2}, 0)[/tex] and [tex]\displaystyle (-\frac{\sqrt{37}}{2}, 0)[/tex].
Asymptotes
- Substitute in variables [Hyperbola Asymptotes]: [tex]\displaystyle (y - 0) = \pm \frac{3}{\frac{1}{2}}(x - 0)[/tex]
- [Hyperbola Asymptotes] (Parenthesis) Subtract: [tex]\displaystyle y = \pm \frac{3}{\frac{1}{2}}x[/tex]
- [Hyperbola Asymptotes] Divide: [tex]\displaystyle y = \pm 6x[/tex]
Our hyperbola asymptotes are y = 6x and y = -6x.